Functional calibration does not improve the concurrent validity of magneto-inertial wearable sensor-based thorax and lumbar angle measurements when compared with retro-reflective motion capture. - Cottam, Daniel S.; Campbell, Amity C.; Davey, Paul C.; Kent, Peter; Elliott, Bruce C.; Alderson, Jacqueline A. (Medical & Biological Engineering & Computing, 2021)
Magneto-inertial measurement unit (MIMU) systems allow calculation of simple sensor-to-sensor Euler angles, though this process does not address sensor-to-segment alignment, which is important for deriving meaningful MIMU-based kinematics. Functional sensor-to-segment calibrations have improved concurrent validity for elbow and knee angle measurements but have not yet been comprehensively investigated for trunk or sport-specific movements. This study aimed to determine the influence of MIMU functional calibration on thorax and lumbar joint angles during uni-planar and multi-planar, sport-specific tasks. It was hypothesised that functionally calibrating segment axes prior to angle decomposition would produce smaller differences than a non-functional method when both approaches were compared with concurrently collected 3D retro-reflective derived angles. Movements of 10 fast-medium cricket bowlers were simultaneously recorded by MIMUs and retro-reflective motion capture. Joint angles derived from four different segment definitions were compared, with three incorporating functionally defined axes. Statistical parametric mapping and root mean squared differences (RMSD) quantified measurement differences one-dimensionally and zero-dimensionally, respectively. Statistical parametric mapping found no significant differences between MIMU and retro-reflective data for any method across bowling and uni-planar trunk movements. The RMSDs for the functionally calibrated methods and non-functional method were not significantly different. Functional segment calibration may be unnecessary for MIMU-based measurement of thorax and lumbar joint angles.